Edukasi Manfaat Baby SPA untuk Perkembangan Motorik Bayi di Desa Pager Agung, Serang, Banten - Rismawati, Rismawati; Qonita, Qonita; Novitasari, Novitasari (IMPACT: Journal of Community Service, 2025)
Baby spa offers numerous benefits for infants, including helping to regulate sleep patterns, stimulating and balancing the hormones cortisol and oxytocin, boosting the immune system to promote better overall health, and stimulating enzymes in the stomach that enhance optimal nutrient absorption. This community service activity was carried out at the Yasmin Baby Spa Outlet in Serang in July 2024, targeting mothers with babies aged 6 to 12 months. The activity was attended by seven mothers, one therapist, and one midwifery student from Bina Bangsa University. The educational session aimed to increase the mothers' knowledge and skills in performing baby massage and baby spa treatments, enabling them to apply these practices independently at home.Based on the evaluation conducted after the session, participants’ knowledge increased by up to 82%. This indicates that the activity had a positive impact in enhancing mothers’ understanding and awareness of the importance of early stimulation through baby massage and baby spa. Moreover, the activity equipped mothers with practical skills that can be directly applied, thus supporting the optimal growth and development of their babies.